2015
DOI: 10.3892/etm.2015.2214
|View full text |Cite
|
Sign up to set email alerts
|

Bushen Zhuangjin Decoction promotes chondrocyte proliferation by stimulating cell cycle progression

Abstract: Bushen Zhuangjin Decoction (BZD), a well-known formulation in Traditional Chinese Medicine, has been widely used for the treatment of osteoarthritis (OA). Due to the poor intrinsic repair capacity of chondrocytes, promoting the proliferation of chondrocytes is an efficient treatment to delay the progression of cartilage degradation. The present study, therefore, focused on the effect of BZD on chondrocyte proliferation, exploring the mechanism of BZD on the inhibition of cartilage degradation. Chondrocytes iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It regulates chondrogenes at different stages in different ways, and plays a crucial role in the physiopathology of OA ( 22 24 ). Altering the expression of genes and proteins in articular chondrocytes is correlated with the pathological process of OA ( 25 ). Several molecular components of the Wnt/β-catenin signaling pathway have been shown to be associated with OA, including Wnt-4, Frizzled-2, β-catenin and GSK-3β.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates chondrogenes at different stages in different ways, and plays a crucial role in the physiopathology of OA ( 22 24 ). Altering the expression of genes and proteins in articular chondrocytes is correlated with the pathological process of OA ( 25 ). Several molecular components of the Wnt/β-catenin signaling pathway have been shown to be associated with OA, including Wnt-4, Frizzled-2, β-catenin and GSK-3β.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it exerts potentially drug-like and multi-target effects ( 37 , 38 ). There is evidence that BZD is effective in the treatment of OA in both clinical and in in vitro studies ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bushen Zhuangjin decoction (BZD) is a well-known formulation that nourishes the Gan (liver) and the Shen (kidney) and also strengthens tendons and bones, and has been long used in China ( 16 ). Clinical studies have demonstrated that BZD has a positive effect on the treatment of OA, and experimental studies have found that BZD decreases the apoptosis of chondrocytes and promotes chondrocyte proliferation ( 17 , 18 ). However, the specific mechanisms responsible for the inhibitory effects of BZD on ER stress-mediated chondrocyte apoptosis remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Achyranthes bidentata polysaccharides are found in chondrocytes in vitro to induce G1/S cell cycle transition and type II collagen expression by upregulating the expression of CDK4, CDK6, and Cyclin D1, which are related to the Wnt/ β -catenin signaling pathway [ 94 ]. Bushen Zhuangjin Decoction [ 95 ] and Duhuo Jisheng Decoction [ 96 ] are also found to increase the expression of CDK4, CDK6, and Cyclin D1 and accelerate G1/S cell cycle transition, whereas they decrease the expression of p21. Bauhinia championi (Benth.)…”
Section: Proliferative Activity Of Tcmmentioning
confidence: 99%